Effect of Anion Size on Conductivity and Transference Number of Perfluoroether Electrolytes with Lithium Salts. Issue 14 (15th November 2017) - Shah, Deep B.; Olson, Kevin R.; Karny, Adar; Mecham, Sue J.; DeSimone, Joseph M.; Balsara, Nitash P.
Abstract : Mixtures of perfluoropolyethers (PFPE) and lithium salts with fluorinated anions are a new class of electrolytes for lithium batteries. Unlike conventional electrolytes wherein electron-donating oxygen groups interact primarily with the lithium cations, the properties of PFPE-based electrolytes appear to be dependent on interactions between the fluorinated anions and the fluorinated backbones. We study these interactions by examining a family of lithium salts wherein the size of the fluorinated anion is systematically increased: lithium bis(fluorosulfonyl)imide (LiFSI), bis(trifluoromethanesulfonyl)imide (LiTFSI) salts and lithium bis(pentafluoroethanesulfonyl)imide (LiBETI). Two short chain perfluoroethers (PFE), one with three repeat units, C6-DMC, and another with four repeat units, C8-DMC were studied; both systems have dimethyl carbonate end groups. We find that LiFSI provides the highest conductivity in both C6-DMC and C8-DMC. These systems also present the lowest interfacial resistance against lithium metal electrodes. The steady-state transference number ( t + ss ) was above 0.6 for all of the electrolytes and was an increasing function of anion size. The product of conductivity and the steady-state transference number, a convenient measure of the efficacy of the electrolytes for lithium battery applications, exhibited a maximum at about 20 wt% salt in all electrolytes. Amongst the systems studied, LiFSI/PFE mixtures were the most efficacious electrolytes.